A Safe, Fibrosis‐Mitigating, and Scalable Encapsulation Device Supports Long‐Term Function of Insulin‐Producing Cells. Issue 8 (13th December 2021) - Liu, Wanjun; Flanders, James A.; Wang, Long‐Hai; Liu, Qingsheng; Bowers, Daniel T.; Wang, Kai; Chiu, Alan; Wang, Xi; Ernst, Alexander U.; Shariati, Kaavian; Caserto, Julia S.; Parker, Benjamin; et al.
Abstract: Encapsulation and transplantation of insulin‐producing cells offer a promising curative treatment for type 1 diabetes (T1D) without immunosuppression. However, biomaterials used to encapsulate cells often elicit foreign body responses, leading to cellular overgrowth and deposition of fibrotic tissue, which in turn diminishes mass transfer to and from transplanted cells. Meanwhile, the encapsulation device must be safe, scalable, and ideally retrievable to meet clinical requirements. Here, a durable and safe nanofibrous device coated with a thin and uniform, fibrosis‐mitigating, zwitterionically modified alginate hydrogel for encapsulation of islets and stem cell‐derived beta (SC‐β) cells is reported. The device with a configuration that has cells encapsulated within the cylindrical wall, allowing scale‐up in both radial and longitudinal directions without sacrificing mass transfer, is designed. Due to its facile mass transfer and low level of fibrotic reactions, the device supports long‐term cell engraftment, correcting diabetes in C57BL6/J mice with rat islets for up to 399 days and SCID‐beige mice with human SC‐β cells for up to 238 days. The scalability and retrievability in dogs are further demonstrated. These results suggest the potential of this new device for cell therapies to treat T1D and other diseases. Abstract : A safe, hypo‐immunoreactive, islet encapsulation, long‐term‐functional device (SHIELD) is developed to deliver islets and human SC‐β cells. The SHIELD, featuring a concentric configuration and a thin, uniform, fibrosis‐mitigating, durable hydrogel coating of zwitterionically modified alginate, is scalable, retrievable, and achieves normoglycemia in diabetic mice for up to 399 days, showing promise for immunosuppression‐free cell therapies for type 1 diabetes.